Suntik TT (Tetanus Toksoid) Yang Dijadikan Syarat Administrasi Nikah Ditinjau Dari Konsep Maslahah Mursalah - Sri Utami Widia Ningsih (Journal Smart Law, 2023)
In marriage, the bride and groom must fulfill several conditions, both requirements according to Islamic law and administrative requirements in the Office of Religious Affairs (KUA). One of the administrative requirements is to attach a certificate of TetanusToxoid injection obtained from the local Health Center. There is no clear legal provision regarding the obligation to inject Tetanus Toxoid in Islamic law, because the ingredients for the tetanus vaccine are not known to be halal and haram, so it is also necessary to know what the opinion of the clergy regarding vaccines is used as a condition for administering marriage. The administration of the Office of Religious Affairs (KUA) is strongly encouraged to inject Tetanus Toxoid, even if the bride and groom do not injectTetanus Toxoid as evidenced by a Tetanus Toxoid certificate they will be subject to sanctions. That's why in writing this scientific work it is also necessary to know the legal status of the Tetanus Toxoid injection which is used as a requirement for marriageadministration in terms of the Maslahah Mursalah concept. The research method used is library research (Library Research) on Tetanus Toxoid injection which is used as a requirement for marriage administration in terms of the Maslahah Mursalah concept.From the data that has been collected, it is then analyzed using the Usul Fiqh approach because this scientific work includes the arguments and thoughts of the Fukaha, and in thinking or drawing conclusions it uses a deductive thinking method. From the results o this study it was concluded that Tetanus Toxoid injections that have not been regulated inthe terms of Islamic law and are required in the administrative requirements of marriage have a positive impact on the bride and groom. Even though the ingredients of the tetanus vaccine are initially harmful to the body, after going through a neutralization process with insulin, then the harmful ingredients become disease barriers or drugs as immunity. So that such a desire creates Maslahah and keeps mafsadat away from humans. Meanwhile, in terms of Maslahah Mursalah, Tetanus Toxoid injections aim to protect wives from contracting tetanus when having sex with their husbands, anticipating wives who giv birth from tetanus due to less sterile equipment, and protecting babies from contracting tetanus when cutting the umbilical cord possibly due to lack of sterility of the tool or exposed to dirt that is not cleaned immediately